Aberrant expression of p63 in an Adenocarcinoma of the prostate that has metastasized to the oral cavity - Khalid, Rafiq; Ramanathan, Anand; Heng, Tee Lun; Lim, Daniel (Cureus, Inc., 2022)
Metastasis specifically to the oral cavity is uncommon in cases of prostate adenocarcinoma. Only 4% of prostate cancer patients present with metastases to the oral cavity originating from the prostate. In the oral cavity, the mandible is the primary site of metastases. p63 is said to be a reliable marker to distinguish benign from malignant lesions of prostate origin, with benign lesions staining positive and malignant lesions staining negative. However, in rare instances, malignant prostate lesions have shown aberrant expression of p63. This case report highlights such a rare incidence of metastasis of prostate adenocarcinoma to the oral cavity involving the right buccal mucosa and the right side of the mandible and having an aberrant expression of p63 in a 76-year-old Chinese male. A computed tomography (CT) scan and bone scan revealed multiple bone metastases, and in three months, the patient succumbed to the disease. Thus, p63 is not exclusively expressed in benign lesions of the prostate, as the aberrant expression may also be evident in malignant lesions such as prostate adenocarcinoma. Therefore, the determination of benign or malignant lesions of the prostate using p63 must be interpreted with caution.